Systems biology properties of reconstructed networks - Palsson, Bernhard (Cambridge University Press, 2006)
Genome sequences are now available that enable us to determine the biological components that make up a cell or an organism. The discipline of systems biology examines how these components interact and form networks, and how the networks generate whole cell functions corresponding to observable phenotypes. This 2006 textbook devoted to systems biology describes how to model networks, how to determine their properties, and how to relate these to phenotypic functions. The prerequisites are some knowledge of linear algebra and biochemistry. Though the links between the mathematical ideas and biological processes are made clear, the book reflects the irreversible trend of increasing mathematical content in biology education. Therefore to assist both teacher and student, in an associated web site Palsson provides problem sets, projects and Powerpoint slides, and keeps the presentation in the book concrete with illustrative material and experimental results.